2018
DOI: 10.1007/s10637-018-0613-x
|View full text |Cite
|
Sign up to set email alerts
|

GLP overexpression is associated with poor prognosis in Chronic Lymphocytic Leukemia and its inhibition induces leukemic cell death

Abstract: Background Heterodimeric methyltransferases GLP (EHMT1/KMT1D) and G9a (EHMT2/KMT1C) are two closely related enzymes that promote the monomethylation and dimethylation of histone H3 lysine 9. Dysregulation of their activity has been implicated in several types of human cancer. Patients and methods Here, in order to investigate whether GLP/G9a exerts any impact on Chronic Lymphocytic Leukemia (CLL), GLP/G9a expression levels were assessed in a cohort of 50 patients and the effects of their inhibition were verifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…G9a is upregulated in hematological malignancies, for which G9a inhibitors have been identified as promising targets for patient management ( Table 3 ) [ 154 , 155 , 156 , 157 , 158 ]. In T-lymphoblastic leukemia cells (T-ALL), inhibiting G9a activity suppresses cellular proliferation and induces apoptosis by downregulating the expression of Bcl-2 and upregulating the expression of Bax and caspase-3 [ 155 ].…”
Section: G9a In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…G9a is upregulated in hematological malignancies, for which G9a inhibitors have been identified as promising targets for patient management ( Table 3 ) [ 154 , 155 , 156 , 157 , 158 ]. In T-lymphoblastic leukemia cells (T-ALL), inhibiting G9a activity suppresses cellular proliferation and induces apoptosis by downregulating the expression of Bcl-2 and upregulating the expression of Bax and caspase-3 [ 155 ].…”
Section: G9a In Cancermentioning
confidence: 99%
“…In T-lymphoblastic leukemia cells (T-ALL), inhibiting G9a activity suppresses cellular proliferation and induces apoptosis by downregulating the expression of Bcl-2 and upregulating the expression of Bax and caspase-3 [ 155 ]. Likewise, in chronic lymphocytic leukemia, targeting G9a and GLP was shown to stimulate cancer cell death [ 154 ]. In multiple myeloma, G9a fosters ReIB-dependent cancer growth and survival, whereas its depletion reduces the expression of ReIB and increases the expression of pro-apoptotic genes, such as Bim and BMF [ 118 ].…”
Section: G9a In Cancermentioning
confidence: 99%
“…Among those, EHMT2 and COPS7A are promising CLL risk gene candidates. The heterodimeric methyltransferases EHMT1 and EHMT2 have recently been implicated with prognosis of CLL and CLL cell viability(33). COPS7A (previous name COP9) is involved in the Transcription-Coupled Nucleotide Excision Repair (TC-NER) pathway and the COP9 signalosome complex (CSN) is involved in phosphorylation of p53/TP53, JUN, I-kappa-B-alpha/NFKBIA, ITPK1 and IRF8/ICSBP.…”
Section: Resultsmentioning
confidence: 99%
“…G9a and GLP seem to play a critical role in several hematological malignancies such as multiple myeloma (MM) [ 76 ] and both myelocytic [ 77 79 ] and lymphocytic leukemias [ 80 , 81 ] (Fig. 3 ).…”
Section: Oncogenic Functions Of Glp and G9a In Lymphoid Neoplasmsmentioning
confidence: 99%
“…Our group identified overexpression of GLP in samples from CLL patients, and its aberrant expression was associated with a poor prognosis. Additionally, we observed that G9a/GLP pharmacological inhibition markedly induced cell death in CLL cells, demonstrating the role of these methyltransferases as potential targets for treatment and progression control of CLL [ 80 ].…”
Section: Chronic Lymphoblastic Leukemiamentioning
confidence: 99%